2017
DOI: 10.1159/000480403
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Effect of Obesogenic Behaviours on Adiposity in Spanish Children and Adolescents

Abstract: Objective: Little is known about the cumulative effect of obesogenic behaviours on childhood obesity risk. We determined the cumulative effect on BMI z-score, waist-to-height ratio (WHtR), overweight and abdominal obesity of four lifestyle behaviours that have been linked to obesity. Methods: In this cross-sectional analysis, data were obtained from the EnKid sudy, a representative sample of Spanish youth. The study included 1,614 boys and girls aged 5-18 years. Weight, height and waist circumference were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 34 publications
2
33
0
2
Order By: Relevance
“…Our finding is also consistent with result of a study from 12 countries including children aged 9–11 years, where TV time was positively associated with obesity . In studies based on Spanish children, associations between TV time and obesity and abdominal obesity were inconsistent . TV watching reduce the time children spend being physically active .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our finding is also consistent with result of a study from 12 countries including children aged 9–11 years, where TV time was positively associated with obesity . In studies based on Spanish children, associations between TV time and obesity and abdominal obesity were inconsistent . TV watching reduce the time children spend being physically active .…”
Section: Discussionsupporting
confidence: 92%
“…16 Similar findings was observed by a study among US adolescents of 9th through 12th grade students from Youth Risk Behavior Surveillance System (YRBSS). 6 The Spanish enKid and AVENA (Alimentación y Valoracióndel Estado Nutricional de los Adolescentes) study analyzed the cumulative effect of low physically activity, high television time and low meal frequency, low sleep duration only in the AVENA study, and skipping breakfast only in the enKid study on the risk of overweight and obesity in children 17 and adolescent. 17,18 They found that increased number of these obesity promoting behaviors increased the odds of overweight, 17,18 abdominal obesity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations